In Spondylotic Cervical Myelopathy Anterior Cervical Discectomy and Fusion by Peek Cage Without Plate Reinforcement is a Standard Method of Treatment - Islam, Md Anowarul; Parvez, Qamruzzaman; Sarker, SK; Goni, Md Fahad; Rana, Md Masud (Journal of Dhaka Medical College, 2017)
Background: Anterior cervical discectomy with fusion (ACDF) is challenging with respect to both patient selection and choice of surgical procedure. Objective: The aim of this study was to evaluate the clinical outcome of anterior cervical discectomy and fusion with an artificial cage made of polyetheretherketone . Patients and Methods: From January 2012 to January 2016, 40 consecutive patients referred to the Department of spine surgery, Bangabandhu Shekh Mujib Medical University were recruited for the study.Postoperative Clinical outcome assessd with Nurick scale for myelopathy, Odoms criteria for functional outcome and Visual Analogue Scale (VAS) for both neck and arm pain. Radiological fusion was assessed by X-ray. Operative complications were reported. Results: 18 patients were operated for one level discectomy and fusion with PEEK cages and 22 patients for two levels. There were 24 (60%) males and 16 (40%) females. The age of the patients ranged from 30-72 years, a mean ± SD 45±8.34. At the 2 years clinical follow-up, there were significant post operative improvements of Nurick scale, and VAS comparative to preoperative record. According to Odoms criteria, 36/40 patients (90%) were graded excellentgood. Conclusion: Anterior cervical discectomy and fusion with polyetheretherketone (PEEK) cage is an effective treatment of cervical myelopathy having higher fusion rate and lack of donor site morbidity. J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 110-114